2013
DOI: 10.1111/bjd.12137
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in Dutch women with lichen sclerosus

Abstract: There is a considerable delay in diagnosis for female Dutch patients with LS. The Skindex-29 domain scores showed a moderately impaired HRQoL. Women with LS reported a lower generic HRQoL than the average female Dutch population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
82
3
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(92 citation statements)
references
References 31 publications
6
82
3
1
Order By: Relevance
“…The mean age at onset of VLS in our population was 57 years, which is consistent with reports from other series [5,6,8,15]. In spite of the absence of age limits in the enrolment criteria, it must be stressed that the majority of the patients attending our Vulva Unit are adult females, usually older than 20 years, and this could have conditioned our findings.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The mean age at onset of VLS in our population was 57 years, which is consistent with reports from other series [5,6,8,15]. In spite of the absence of age limits in the enrolment criteria, it must be stressed that the majority of the patients attending our Vulva Unit are adult females, usually older than 20 years, and this could have conditioned our findings.…”
Section: Discussionsupporting
confidence: 91%
“…Affected women have an increased risk of genital cancers, with a lifetime risk of developing a squamous cell carcinoma estimated to be 2-5% [4,5]. VLS has a considerable impact on health-related quality of life (QoL) and women with VLS have been found to experience a lower health-related QoL than the general population [6]. The number of symptoms seems to be correlated with the health-related QoL of women with VLS.…”
Section: Introductionmentioning
confidence: 99%
“…The average scores of items within a domain are combined into a domain score. Although a total score (the average of all items combined) of Skindex-29 has not been studied, several studies have reported it [26], and cut-off scores have been used for interpretation. The questions have a recall period of 4 weeks and higher scores indicate lower HRQoL.…”
Section: Methodsmentioning
confidence: 99%
“…These women are severely affected; studies indicates that the disease has a large effect on quality of life and many suffer from sexual dysfunction as well [5,[10][11][12]. Even a small improvement will make a difference for the women and therefore we do think that patch testing these patients is important.…”
Section: Discussionmentioning
confidence: 99%
“…Pruritus, pain and dyspareunia are common symptoms and as a result there may be a complete preclusion of sexual intercourse. Women and young girls with the disease describe restrictions in their lifestyle and a reduced quality of life [5,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%